Correction: Polymeropoulos et al. Enhancing Solar Plant Efficiency: A Review of Vision-Based Monitoring and Fault Detection Techniques. Technologies 2024, 12, 175 - Ioannis Polymeropoulos; Stavros Bezyrgiannidis; Eleni Vrochidou; George A. Papakostas (Technologies)
The authors wish to make the following corrections to this paper [...]